Functional Connectome Dynamics After Mild Traumatic Brain Injury According to Age and Sex - Amgalan, Anar; Maher, Alexander S.; Imms, Phoebe; Ha, Michelle Y.; Fanelle, Timothy A.; Irimia, Andrei (Frontiers in Aging Neuroscience, 2022)
Neural and cognitive deficits after mild traumatic brain injury (mTBI) are paralleled by changes in resting state functional correlation (rsFC) networks that mirror post-traumatic pathophysiology effects on functional outcomes. Using functional magnetic resonance images acquired both acutely and chronically after injury (~1 week and ~6 months post-injury, respectively), we map post-traumatic rsFC changes across 136 participants aged 19-79 (52 females), both within and between the brain’s seven canonical rsFC networks: default mode, dorsal attention, frontoparietal, limbic, somatomotor, ventral attention, and visual. Significant sex-dependent rsFC changes are identified between (A) visual and limbic, and between (B) default mode and somatomotor networks. These changes are significantly associated with specific functional recovery patterns across all cognitive domains (p < 0.05, corrected). Changes in rsFC between default mode, somatomotor, and ventral attention networks, on the one hand, and both temporal and occipital regions, on the other hand, differ significantly by age group (p < 0.05), and are paralleled by significant sex differences in cognitive recovery independently of age at injury ((p < 0.05). Whereas females’ networks typically feature both significant (p < 0.036, corrected) and insignificant FC changes, males more often exhibit significant rsFC decreases between networks (e.g., between dorsal attention and limbic, visual and limbic, default-mode and somatomotor networks, p < 0.0001), all such changes being accompanied by significantly weaker recovery of cognitive function in males, particularly older ones (p < 0.05). No significant FC changes were found across 35 healthy controls aged 66 to 92 (20 females). Thus, male sex and older age at injury are risk factors for significant rsFC alterations whose patterns underlie post-traumatic cognitive deficits. This is the first study to map, systematically, how TBI impacts rsFC between major human functional networks.